EVALUACIÓN PARA EL DESEMPEÑO DEL TALENTO HUMANO DE LA GERENCIA FINANCIERA EN LA EMPRESA ELÉCTRICA REGIONAL DEL SUR S. A. DE LA CUIDAD DE LOJA - Cueva Mena, Hugo Bernabé (2015)
The current thesis denominated EVALUACIÓN PARA EL DESEMPEÑO DEL TALENTO HUMANO DE LA GERENCIA FINANCIERA EN LA EMPRESA ELÉCTRICA REGIONAL DEL SUR S. A. DE LA CUIDAD DE LOJA was developed to meet prior to obtain the degree of Engineer in Business Administration requirement, according to the academic system of the Universidad Nacional de Loja . During the development of this thesis the used process to implement the performance assessment coded according to the ministry of labor relations entity showed through their website shows the automated form called MRL-EVAL-01. Their study focuses on the verification of compliance with the objectives, for which a performance evaluation human talent of financial management was applied by means of indicators to measure the efficiency and efficacy, and to know how they are fulfilling their duties in accordance with the rules and regulations governing the institution. According to Article 22 of the MRL standard performance evaluations are: excellent, very good, satisfactory, poor and unacceptable. Determined according to the percentage rating as follows: EXCELENT.- High performance, whose rating was achieved less than 90.5%. VERY GOOD.- Better than expected performance, rating between 80.5% and 90.4%. SATISFACTORY.- Expected performance, qualification it is between 70.5 and 80.4%.POOR.- Performance below expectations, a rating that is 5 committed between 60, 5% and 70.4%. UNACCEPTABLE. - Performance at very low expectations, rating equal to or less than 60.4%. The methodology used for conducting the research is as follows: analytical method, scientific, descriptive: gathering relevant information that allowed the current situation of the institution. For the implementation of the evaluation process, CFO established the space required to jointly can carry out an interview survey, indicators, and the number of activities to be performed by the evaluator: the end of the evaluation period immediate supervisors undertake the qualification process and corresponding check entering numerical values or by selecting the predetermined factors that exist in automated form to enter the data is converted into percentage, thereby determining the rating achieved by the server as a result of evaluated performance evaluation. At the end of the research report was presented to the Executive President, consisting in the conclusions and recommendations, reasonably valid, appropriate to help the improvement of the institution.